THE NEUROPATHY SPECTRUM IN WALDENSTRöM'S MACROGLOBULINAEMIA. Issue 11 (14th October 2015) - Carr, Aisling; Jaunmuktane, Zane; Brandner, Sebastian; Kothari, J; Blake, Julian; D'Sa, Shirley; Lunn, Mike
Abstract : Background: UK WM Guidelines recognise 2 mechanisms of nervous system involvement either direct tumour invasion of the CNS or antibody mediated damage to peripheral nerves. We present 5 cases illustrating an extended diversity of PNS involvement in WM with implications for treatment and outcome. Cases: A 73 year-old man (IgMκ WM) developed progressively disabling tremor with stable WM. Neurophysiology was demyelinating with disproportionate DMLs; anti-MAG antibodies were strongly positive. He was treated with DRC with symptom stabilisation. A 64 year-old woman (IgMκ) with typical anti-MAG neuropathy developed severe episodic foot pain and ulceration. Skin biopsy confirmed leucocytoclastic vasculitis. She was treated with DRC but died from sepsis. A 43 year-old man (IgMκ WM) with rapidly progressive sensorimotor neuropathy had lymphplasmacytoid cellular infiltrate in sural nerve. He was successfully treated with IDARAM. A 59 year-old man (IgMλ WM) developed small then large fibre axonal neuropathy with autonomic symptoms within 2 years. A SAP scan showed moderate kidney uptake. MRI neurography directed biopsy and confirmed amyloid. Palliative treatment was offered. A 70 year-old woman (IgMλ WM) developed severe burning pains in her feet and became ataxic 2 months later. Sural nerve biopsy confirmed endoneurial amyloid. DRC was given. Discussion: These cases highlight the importance of accurate diagnosis in WM-associated neuropathy. We propose a novel diagnostic algorithm.